2020
DOI: 10.3390/ma13194358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Geometrical Parameters of Dolomite Coarse Aggregate on the Thermal and Mechanic Properties of Preplaced Aggregate Concrete

Abstract: The article shows investigations on the behavior of preplaced aggregate concrete with regular and irregular coarse aggregates. The thermal properties, compressive strength, and internal structure were analyzed based on computed tomography images. The regular and irregular shapes of aggregates were obtained according to patented technology, which is possible to produce in both laboratory and industrial conditions. Based on the conducted calculations, heat storage capacity was assessed. The influence of grain sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Brick and sand have an even lower volumetric heat capacity at about 1,200,000 J/(m 3 K). For normal and refractory concrete with a density of about 2400 kg/m 3 , the volume heat capacity is about 2,770,000 J/(m 3 K) [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Brick and sand have an even lower volumetric heat capacity at about 1,200,000 J/(m 3 K). For normal and refractory concrete with a density of about 2400 kg/m 3 , the volume heat capacity is about 2,770,000 J/(m 3 K) [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…More results can be found in concrete separation especially the materials from demolition of building constructions [15,16]. Despite of that the problem of aggregate segregation is significant, because it influences improvement of qualitative characteristics of final products, through elimination of weaker and partially damaged particles, as well as weathered grains [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…It also concluded that the shape parameters affect the mechanical properties of the asphalt mixtures. With enormous technological growth worldwide, digital image analysis technology has become an effective tool to efficiently quantify the major aggregate shape, texture, and other parameters [39]. These parameters are either for the form or aggregate angularity.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that this technique could be applied to detect the more accurate shape properties, and it is more suitable for the shape characterization of aggregate particles. Stempkowska, Gawenda [39] utilized computer tomography to detect the internal structure of the concrete mixes. It was concluded that the arrangement and shape of the aggregates have a significant impact on the performance of the hardened concrete.…”
Section: Introductionmentioning
confidence: 99%